Optimization of Ultra Lightweight Mirror and Opto-Mechanical–Thermal Coupling Analysis Based on Solar Thermal Radiation - Quanliang Dong; Jinhe Yang; Tong Zhang; Xiaoming Wang (Sensors)
To improve maneuverability, the focus of photoelectric theodolites is on reducing the weight of the primary mirror and enhancing its optical performance. This study uses MOAT and Sobol methods to identify key parameters that affect design. Using the high-sensitivity part as the optimization domain, six optimization results were obtained based on the multi-objective SIMP topology optimization method and synthesized into a compromise optimization structure. The performance of the mirror before and after optimization was compared on the opto-mechanical–thermal level. Modal analysis shows the optimized structure has a first natural frequency of 716.84 Hz, indicating excellent stiffness and avoiding low-frequency resonance, with a 30.37% weight reduction. Optical performance is also improved, with a 6 μm reduction in the spot diagram radius and an 8.95 nm decrease in RMS. Simulations under real-world conditions show that the lightweight mirror performs better in resisting gravity deformation and maintaining imaging quality. At maximum thermal deformation, the spot diagram radius of the optimized mirror is 1521.819 μm, with only a 0.145% difference in imaging quality compared to the original. In conclusion, the optimized structure shows comprehensive advantages. Constructing the optical system components and the real physical environment of the site provides a valuable reference for the optimization and analysis of the mirror.